The Cross fit Training on Some Physical Abilities in Fitness Participants Aged 25 – 35 Years Old - Ali, Ishraq; Abed alnabi, Noor (Journal of Physical Education, 2019)
The research problem lies on that exercise in most physical fitness centers depends heavily on the individual’s performance of the exercises given to him with no care to the element of competition, which is a key element in CROSS FIT training. The researchers used the experimental method on subjects of (16) female fitness participants that were equally divided into experimental group (the cross fit group), and the controlling group the Aerobics Group. The researchers concluded that cross fit training developed some physical abilities in fitness participants. Finally the recommended paying attention to Cross fit training and work on the development of training curriculums to develop physical abilities.